Presence D’un Decor Antique Sur Des Dirhams Umayyades "II/VIII Siecle": Dirhams D’Al Mubaraka - Ghodhbane, Mohamed (الجمعية التونسية لعلم الآثار, 2016)
Among the Umayyad dirhams, emissions from two consecutive years, 107 H. and 108 H. in the name of al-Mubaraka, have two decorative motifs widespread during antiquity. Using its grounds highlights the survival of ancient decorative repertoire and thanks to several factors including cultural exchanges and mutual artistic influence. With the al-Mubaraka toponym the grounds are a rich study material to try to unlock the secrets of their choice while trying to put them in their situation.
Keywords: الآثار الإسلامية -- العصر الأموي -- المسكوكات الإسلامية -- الزخرفة الإسلامية -- الدرهم الأموي